DINAMIKA KEPEMIMPINAN KEPALA DESA DALAM MENANGANI PERMASALAHAN PEMERINTAHAN DI DESA BOJONGGEDANG KECAMATAN RANCAH KABUPATEN CIAMIS - Repa Nurlaela; Dini Yuliani; Fahcmi Syam Arifin (JURNAL ILMIAH NUSANTARA, 2025)
This research is motivated by the suboptimal leadership of the Village Head in handling governmental issues in Bojonggedang Village, Rancah District, Ciamis Regency. The purpose of this study is to determine the dynamics of the Village Head's leadership in handling governmental issues in Bojonggedang Village, Rancah District, Ciamis Regency. The research method used is qualitative research with descriptive analysis. The results of the study indicate that the Village Head's leadership in handling governmental issues in Bojonggedang Village, Rancah District, Ciamis Regency is still suboptimal. This is due to several obstacles, namely the lack of community participation causing the Village Head to make decisions less effective and efficient, the lack of ability to motivate subordinates, the lack of communication between the Village Head and subordinates and the community, the suboptimal utilization of subordinates' abilities, the lack of responsibility of the Village Head to subordinates because there are still subordinates who are not responsible for their duties and functions, and the lack of emotional control. This research can improve the effectiveness of the Village Head's leadership and the government, policy development, public service improvement, and capacity building of the Village Head to improve leadership abilities in handling governmental issues.